Influence of School Feeding Programs on Student Attendance and Academic Performance in Ghana, and Its Potential as a Model for Other West African Nations - John, Jerry John (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to evaluate the influence of school feeding programs on student attendance and academic performance in Ghana, and its potential as a model for other West African nations Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Influence of school feeding programs in Ghana reveals that these initiatives significantly improve student attendance and academic performance, particularly in underserved and rural areas. By providing daily meals, the programs help reduce hunger, improve concentration, and boost overall participation in school activities. Attendance rates have notably increased as families are more motivated to send their children to school, knowing meals are provided. Unique Contribution to Theory, Practice and Policy: Maslow’s hierarchy of needs theory, human capital theory & social ecological model (SEM) may be used to anchor future studies on the influence of school feeding programs on student attendance and academic performance in Ghana, and its potential as a model for other West African nations. To maximize the impact on both attendance and academic performance, programs should focus on improving the nutritional content and consistent delivery of meals. Ghana’s school feeding program should serve as a policy model for other West African nations, but adaptations must be made to fit the specific contexts of each country.